RELATIONSHIP BETWEEN PERFORMANCE EXPECTANCY AND BEHAVIORAL INTENTION: A SYSTEMATIC LITERATURE REVIEW - Firmannudin, Firmannudin; Sartika, Dewi; Ayu Safitri, Fikta Novia; Parlina, Tika (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
The aim of this article is to analyze and comparing preview studies of relationship between performance expectancy and behavioral intention.